موقف بإسقاط التكاليف الشرعية عند أقطاب الصوفية: تحلیل نقدی: Concept of Abolition of Certain Duties of Sharīʻah for the accomplished Sufis: A Critical Analysis (Al-Qamar, 2019)
This article discusses the question whether the accomplished Sufis are innocent and are exempted from duties of Sharīʻah? It argues that obligations of Sharīʻah are the same for Sufis and general Muslim community. There are no exceptions to the Sharīʻah rules for Sufis.  Details of the forms and the manner of observance of four basic Islamic tenets duties (Imāniāt, Aḥkām, Ibādāt and Akhlāqiāt) enunciated in the Holy Quran, Ḥadīth and the books of Fiqh are identical for all Muslims.  Sufis, like other Muslims, have to follow all the relevant commandments. It highlights the point that every Sufi is not authorized to practice Ijtihād and issue certain Fatwa. However it proclaims that the mistake of one Sufi cannot be taken as the mistake of all Sufis.
Keywords: Sufis; duties of Sharīʻah; elimination